2004
DOI: 10.1186/1465-9921-5-10
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of airway injury in an epithelial model of mucociliary clearance

Abstract: We studied the action of sodium metabisulphite on mucociliary transport in a frog palate epithelial injury model, hypothesizing that it may be useful for the study of mechanisms of airway injury. Sodium metabisulphite (MB) releases SO 2 on contact with water. SO 2 is a pollutant in automobile fumes and may play a role in the exacerbation of airway disease symptoms. We first investigated its effect on mucociliary clearance. MB 10 -1 M, increased mucociliary clearance time (MCT) by 254.5 ± 57.3% of control value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
3
Order By: Relevance
“…We have shown that sustained activation of the kinase can autodownregulate PKCε, and we propose that effective inhibition of PKCε induces ciliated cell detachment. Several other in vitro treatments, including incubation of ciliated cells with sodium metabisulfite, can also slow ciliary beat and induce ciliated cell detachment at high concentrations [24]. Furthermore, neuropeptide Y was found to inhibit CBF in cultured human BECs, presumably mediated through a novel PKC isoform-mediated pathway [25].…”
Section: Discussionmentioning
confidence: 97%
“…We have shown that sustained activation of the kinase can autodownregulate PKCε, and we propose that effective inhibition of PKCε induces ciliated cell detachment. Several other in vitro treatments, including incubation of ciliated cells with sodium metabisulfite, can also slow ciliary beat and induce ciliated cell detachment at high concentrations [24]. Furthermore, neuropeptide Y was found to inhibit CBF in cultured human BECs, presumably mediated through a novel PKC isoform-mediated pathway [25].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, O'BRIEN et al [45] examined the action of SO 2 on mucociliary transport in a frog palate epithelial injury model. They used sodium metabisulfite, which releases SO 2 on contact with water.…”
Section: Somentioning
confidence: 99%
“…45 Conhecer a resposta do transporte mucociliar em pacientes com DPOC frente ao exercício físico é essencial a todos os profissionais envolvidos em reabilitação pulmonar e que prescrevem exercício físico no tratamento de DPOC, visto que o transporte mucociliar é a primeira linha de defesa do sistema respiratório contra agentes agressores e irritantes e sua integridade está inteiramente relacionada à diminuição de risco de infecções respiratórias que possuem impacto extremamente negativo nos pacientes com DPOC, pois aumentam o risco de exacerbações. 1,2,7,36 Deste modo o presente estudo pôde concluir que pacientes com DPOC apresentaram aceleração da transportabilidade mucociliar frente á uma sessão de exercício aeróbio e que não foi possível observar uma associação da modulação autonômica nesta resposta após o exercício.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…1 O funcionamento adequado do transporte mucociliar depende da estrutura, sincronia e frequência do batimento ciliar, quantidade e qualidade da secreção brônquica e da perfeita interação entre estes componentes. [3][4][5][6][7] Algumas condições como processos inflamatórios e exposição excessiva de partículas inaladas são capazes de alterar a eficiência do batimento ciliar. 8,9 Além disso, sabe-se que em indivíduos saudáveis a realização aguda de exercício físico promove uma aceleração da transportabilidade mucociliar.…”
Section: Intr Intr Intr Intr Introdução Odução Odução Odução Oduçãounclassified
See 1 more Smart Citation